Quantifying Health State Utilities for Permanent Dentition: A Cross-Sectional Study - Yazeed Alharthi; Osama Alasmari; Hamad Almuaiqly; Saif Alhumaidi; Amjad Alemam; Wahdan Elkwatehy; Omair M. Bukhari (Hindawi Limited, 2022)
Introduction. Health utility represents individual preference strengths regarding health-related outcomes as a numerical value, with higher utility values of a health state achieved by a service or treatment strategy suggesting that it is more worthwhile to implement and allocate resources to this service. This study aimed to find and compare the utilities of permanent teeth-related health state outcomes. Materials and Methods. Two groups, one of the dentists (50) and another of dental patients (50), responded to a standard gamble questionnaire to determine the utilities of four hypothetical alternatives of dental health state as follows: (1) carious posterior tooth with pain, (2) carious posterior tooth without pain, (3) filled posterior tooth with a temporary restoration, and (4) filled posterior tooth with a permanent restoration. Values were calculated and compared between the two groups using the unpaired Student's t-test, and another comparison between gender groups was performed using a one-way analysis of variance. Results. There were significant differences between dentists and patients regarding health states 2, 3, and 4 (p = 0.011, 0.026, and 0.008, respectively). However, there were no significant differences between men and women regarding all health statuses. Nonetheless, there were significant differences between male dentists and male patients for health statuses 1 and 3 (p = 0.047 and p = 0.036), respectively. Conclusion. The oral health-related quality of life and its relation to economic dentistry is essential aspects of our modern practice. In the present study, there was a statistically significant difference in the utility value reported by dentists and patients. However, more research is needed in this area.